Patients' satisfaction and quality of life in coronary artery disease - Asadi-Lari, M.; Packham, C.; Gray, D. (2003)
OBJECTIVES: To assess satisfaction of survivors of coronary artery diseases (CAD) with healthcare services and to determine whether specific components of standard health-related quality of life (HRQL) assessment tools might identify areas of satisfaction and dissatisfaction. METHOD: A specific tool developed to provide a comprehensive assessment of healthcare needs was administered concomitantly with generic and specific HRQL instruments, on 242 patients with CAD, admitted to an acute coronary unit during a single year. RESULTS: 92.5% of patients confirmed their trust in and satisfaction with the care given by their General Practitioner; even so, one third experienced difficulty getting an appointment and a quarter wanted more time for each consultation or prompt referral to a specialist when needed. Around a third expressed dissatisfaction with advice from the practice nurse or hospital consultant. Overall 54% were highly satisfied with services, 33% moderately satisfied and 13% dissatisfied.Cronbach's alpha was 0.87; the corrected total-item correlation ranged between 0.55-0.75, with trivial 'floor' score and low 'ceiling' effect. Several domains in all three HRQL tools correlated with items relating to satisfaction. The Seattle Angina Questionnaire Treatment Score correlated significantly with all satisfaction items and with the global satisfaction score. CONCLUSION: Cardiac patients' demanded better services and advice from, and more time with, health professionals and easier surgery access. The satisfaction tool showed acceptable psychometric properties. In this patient group, disease-specific HRQL tools seem more appropriate than generic tools for surveys of patient satisfaction